Wheat scenario in India- Transition from the green revolution to the present - Singh, S S (Indian Farming, 2015)
The present yield plateau is the major concern for achieving the targeted wheat production of 109 mt by 2020. However, bridging the yield gap between experimental and farmers’ fields can solve the problem to a considerable extent. With the existing technologies, about 29.4 mt wheat can be added to the nationalbasket. For future needs, the genetic enhancements of yield potential through integration of conventional and molecular approaches with special reference to the changing climaticconditions, integrated management of resources and incorporation of resistance genes to various biotic and abiotic stresses are very significant factors. Quality of wheat willcontinue to be one of the major foci of research. With support from farmers, policy makers and extension units, it is expected that present technologies can be further refined and popularized so that wheat production can be enhanced to meet our future demand for the food and nutritional security.